Profesi Byoujihoikusi dalam Manga 37.7º no Namida Karya Shiina Chika - Juni Arsih, Ni Kadek (Humanis, 2018)
T his research entitled "Byoujihoikushi Profession in 37.7º no Namida  Comics Written by Shiina Chika”. This research aims to determine byoujihoikushi task and the qualification needed byoujihoikushi that illustrated in 37.7º no Namida comic . Theory that used for analyzing is the theory of sociology of literature proposed by Ian Watt. The results of this research showed that there are three ways of handling a child hurt by the byoujihoikushi, which consists of pleading the byoujihoikushi done by the parents of the child, and the byoujihoikushi taking over the parental role. There are four tasks that must be done by the byouihoikushi and there are three qualification needed byoujihoikushi that reflected in 37.7º no Namida c omics.